Youth knowledge and perceptions of climate mitigation - Ylva Andersson; Shane Timmons; Pete Lunn (The Economic and Social Research Institute (ESRI), 2022)
Five hundred young people (aged 16 to 24 years) took part in a short, online study about the environment. The study focused on knowledge and beliefs about climate change mitigation. We recorded the climate-friendly behaviours young people in Ireland report engaging in, as well as their knowledge of the relative mitigative potential of different actions (e.g. eating a plant-based diet, avoiding flying). The study included a controlled experiment where we tested the effects of information about the correct impact of said actions on motivation to act in climate-friendly ways. We also measured how much they believe different groups (young people in general, older people, the government) can mitigate the worst effects of climate change and how much responsibility they attribute to each group. The study also assessed engagement with local outdoor amenities and any barriers to engagement, which allowed us to explore relationships between engagement with nature and broader climate change beliefs. The study was conducted in March 2022 and is the first of its kind in Ireland.
Keywords: 330; Klimapolitik; Klimaschutz; Wissen; Wahrnehmung; Umweltbewusstsein; Jugendliche; Junge Erwachsene; Irland